Metapragmatic Evaluation of Verbal Irony by Speakers of Russian and American English - Shilikhina, Ksenia (Research in Language, 2012)
The paper discusses metapragmatic assessment of verbal irony by speakers of Russian and American English. The research combines ideas from metapragmatics, folk linguistics and corpus linguistics. Empirical data are drawn from the Russian National Corpus (RNC), the Corpus of Historical American English (COHA) and the Corpus of Contemporary American English (COCA). Spontaneous evaluation of linguistic behavior is an important function of both explicit and implicit metapragmatic uses of language. Distributional adjectival patterns of the Russian word ирония and English irony are treated as implicit indicators of folk metapragmatic awareness. Connotations of the adjectives reflect our everyday linguistic practices and contribute to the vagueness of the notion and the definition of irony in scholarly theorizing.